Structural Model of Principals' Innovative Leadership Attributes on Managerial Creativity - Yousif Alsuwaidi, Khawla Ahmed Khalifa; Omar , Abdul Jalil (International Journal of Sustainable Construction Engineering and Technology, 2020)
UAE educational institutions had being underpinned and characterized by a series of challenges such as weak student achievement, inadequate levels of education, insufficient number of teachers, poor school management and lack of professionalism. Also the schools in the UAE continue to be plagued with poor infrastructure and organizational culture. This research was conducted to determine factors affecting the principals’ innovative leadership attributes on managerial creativity in UAE. A total of 230 questionnaires were distributed out of which 167 (72.3%) were successfully retrieved. The data collected were Analysis of Moment Structures Equation Modelling (AMOS-SEM). The structural model was developed based on 8 groups of factors that affecting the managerial creativity of the educational institutions which are: innovative leadership attributes; risk tolerance; domain expertise; openness; emotional stability; confidence; action oriented and professional development. The developed model was statistically validated as it achieved all the criteria of goodness of fit. Beside that all the hypotheses are significant meaning that the eight groups have significant impact to the managerial creativity. Hopefully if the model is implemented persistently, it is believed to be able to improve the managerial creativity in the UAE. Any attempt to improve professional development in the relationship between the creative leadership qualities of principals and managerial innovation in the UAE it good to refer to this model.